Compatibilisation of NR/PVC blend with graft copolymers of NR - Gupta Subhranshu; George Benny; Khastgir Dipak; Kuriakose Baby; Varkey Jacob K (International Seminar on Advances in Polymer Technology, 16-17, January 2004, Cochin University of Science and Technology, Kochi,.p.28-29.)
Polymer blends are frequently used in industry to obtain the best compromisr in the physical properties, processibility and cost of the compound. One commercially important and miscible polymer blend is Nitrile Rubber (NBR) with Poly Vinyl Chloride (PVC). However, blends of PVC with Natural Rubber (NR) in all compositions were found to be incompatible and showed poor mechanical properties. Miscibility between the constituent polymers is often a necessity for forming successful blends. Therefore ternary components are often used, showing compatibilising action, by polar interaction, chemical reaction or by better interfacial adhesion, achieved through interface modification. Therefore in NR/PVC blend, a part of NR was replaced by graft copolymer of NR having a polar segment to compatibilise with PVC phase of the blend. As the graft copolymer of NR contains some remaining unsaturation, therefore it can take part in cross linking with the NR phase present in the blend system, when the blended material was vulcanized, using usual sulphur vulcanization procedure. Therefore, the graft copolymer of NR will bridge between polar phase of the blend in one hand and the non polar phase on the other hand. It was found that, due to better adhesion between two phases, we are getting 17;increment in Tensile Strength & 104;increment in 300;Modulus for modified blend compare to unmodified blend. At the same time Tear strength was also increased by 54;for a compatibilised blend.
Keywords: Graft polymers; NR/PVC blend; Polymer blends